35 Percutaneous coronary intervention in patients with acute coronary syndrome. (24th April 2016) - Carter, Paul; Baig, Mudassar; Mavi, Jaskaran; Ali, Noman; Aziz, Amir; Uppal, Hardeep; Chandran, Suresh; Sarma, Jaydeep; Potluri, Rahul
Abstract : Introduction: Percutaneous Coronary Intervention (PCI) has changed the management of acute coronary syndrome (ACS). However, the role of PCI in patients with previous coronary artery bypass grafting (CABG) is widely debated. Lack of clear guidelines leads to subjective assessments based on clinician preferences. We sought to investigate if PCI affected all-cause mortality in ACS patients with previous CABG. Methods: Completely anonymous information on patients with ACS with a background of previous CABG presenting to three multi-ethnic general hospitals in the North West of England, United Kingdom in the period 2000–2012 was obtained. Patients were traced using the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) study protocol using ICD-10 and OPCS-4 coding systems. Information on demographics, co-morbidities and procedures were available for all patients. Predictors of mortality and survival analyses were performed using SPSS version 20.0. Results: Out of 12, 227 patients with ACS, 1172 (19.0%) cases had previous CAVBG. Of these 83 (7.1%) patients underwent PCI. Multi-nominal logistic regression, accounting for differences in age and co-morbidities, revealed that PCI conferred a 7.96 times improvement in mortality (2.36–26.83 95% CI) compared to not having PCI. Conclusions: We have shown that PCI confers significantly improved all-cause mortality in the management of ACS in patients with previous CABG. This highlights the need for clinicians to conscientiously think about the individual benefits and risks of PCI for every patient.